Estudos de parâmetros de propagação de fermento (Saccharomyces cerevisiae) para produção de cachaça de alambique - Helia Lucila Malta (2006)
Cachaça, a typical Brazilian product, has been prominent in the economy of the state of Minas Gerais. Traditionally, the propagation of yeast in distilleries of cachaça occurs directly in the vats of fermentation, which are not appropriate for the aerobic phase (yeast propagation), because they do not possessing aeration and agitation devices. The introduction of a specific equipment to optimize the propagation stage of yeasts, can also open the way for use of selected yeasts. In this work three types of equipment for propagation of Saccharomyces cerevisiae were tested; studyng the effect of the addition of air, nutrients and micronutrients on the viability and cellular growth, yield of cellular mass and the substrate conversion factor in cells. Under the evaluated conditions, the use of ammonium sulphate as a nitrogen source was not sufficient to maintain the viability of the cells, result obtained with yeast extract in the concentration of 0,9 g/100 mL. The minerals tested (zinc, iron, copper and manganese sulphates) did not interfere with the Yx/s factor, the increase in cellular mass and the viability. The initial concentration of inoculum was a decisive factor in the increase in cellular mass, resulting increase of up to 75 times the initial mass.